Customer satisfaction with bank care - Lima, Euder Ramos (2021)
Customer satisfaction can be understood as the feeling of contentment or disappointment over the expectation created for a given product or service. The objective of this study was to understand customer satisfaction with the service provided by the bank "X" located in a city of the Interior of Bahia. We used the qualitative interpretive approach of the field research type, having as clients of an agency of the "X" bank located in a city of the Interior of Bahia, having been interviewed 13 clients, doing it through open questions for more precise collection and complete data. With the answers of the interviews, a content analysis of the data in the thematic modality was performed. The results show that customers are satisfied with the quality of the services provided directly by the employees besides the services offered in alternative channels such as Internet Banking and the service by the Cellular. In a general context the study concluded that the interviewees were satisfied with the services provided by the Banking Agency.